ANALISIS DE LA DROGADICCION Y SUS EFECTOS PSICOSOCIALES Y SU PREVENCION EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA “EMILIANO ORTEGA ESPINOZA” DEL CANTON CATAMAYO - Macas Criollo, Natalia Silvana (2019)
Drug addiction is a social problem that affects the organism of the human being, producing alterations in the physical, mental, psychological state, which can begin with the experimental consumption of a recreational drug in social situations that become daily and frequent. This social problem manifests itself more in adolescents harming, their personal, family and social, many of these cases due to the influence of bad companies, lack of family communication, among others; that is why through this research entitled "Analysis of drug addiction and its prevention in the students of the educational unit" Emiliano Ortega Espinoza "of Catamayo"; objectives were set in order to know what are the causes that influence students to consume these substances, and through this to propose an intervention which provides alternative solutions and prevention for the purpose of this research. The process of this research was carried out through the use of scientific, deductive, inductive, analytical, and synthetic methods, as well as the use of techniques and tools such as interviews, focus groups, observation sheets, which facilitated the collection of information, to then elaborate the intervention proposal. Among the main findings is that the main factor for the consumption of psychotropic substances are family problems, lack of communication and poor decisions; that leads them to drug use. On the other hand, the prevention of these types of substances is not articulated with the State regulations that ensure a true participation of the Educational Institution and families, in order to avoid this problem. Finally, there is the proposed intervention called " Be yourself, say no to drugs " proposal that closes with an affective process.